Compressive Optic Neuropathy Caused by Orbital Non-Hodgkin's Lymphoma - Mohammed M. Ziaei; Hadi Ziaei (Case Reports in Ophthalmological Medicine)
Purpose. To present a unique case of Non-Hodgkin’s-Lymphoma- (NHL) associated compressive optic neuropathy. Method. An 89-year-old male presenting with acute unilateral visual loss and headache. Results. Patient was initially diagnosed with occult giant cell arteritis; however after visual acuity deteriorated despite normal inflammatory markers, an urgent MRI scan revealed an extensive paranasal sinus mass compressing the optic nerve. Conclusion. Paranasal sinus malignancies occasionally present to the ophthalmologist with signs of optic nerve compression and must be included in the differential diagnosis of acute visual loss.